Fluvial sole structures from the Siwalik Group, north Pakistan - Abbasi, Iftikhar Ahmed; Friend, Peter F. (Journal of Himalayan Earth Sciences, 1993)
The Siwalik Group consists of over 6 km of fluvial clastic sediments. Fluvial cycles of thick sandstone (5-20 m) and siltstones (5-50 m) are common particularly in the Chinji Formation. Sole structures are well developed on the base of the sandstone bodies and represent an early phase of erosion of the overbank fines related to channel evulsion before deposition of major sandstone. Examples from the Chinji and Shakardarra formations include gutter casts, crescent marks, and flute marks all due to aqueous scour. Polygonal marks and pedestal structures, metres across, and locally metres in relief, may be sub-aqueous or sub-aerial in origin.